Influence of Fly Ash content in Aluminium matrix composite produced by stir-squeeze casting on the scratching abrasion resistance, hardness and density levels. (2017) - Bharathi, V.; Ramachandra, M.; Srinivas, S.
Abstract: Aluminium matrix composite consisting up to 5% weight percentage of fly-ash particles was investigated by synthesizing using stir-squeeze cast method. Three body abrasive wear tests were carried out to assess the abrasive wear resistance of the composite against various speeds and loads. Wear resistance of the composite found to increase with increase in fly ash particles whereas wear rate has increased with increase in load and speed. Further by using Taguchi's technique the results were tabulated in Minitab – 17 software package to analyse the effect of each input parameter on the wear rate. Further Optical microstructural and SEM studies were also carried out to find out the pattern of distribution of fly ash particles in the matrix of aluminium and to carry out the analysis of the worn surfaces.